The effect of ESG on financial performance of energy sector companies in Indonesia and Malaysia during 2020–2023 - Nawangsari, Ajeng Tita; Fachrezzi , Bima Rafly; Masruroh, Auliyatul (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
The study seeks to examine how Environmental, Social, and Governance (ESG) disclosure influences financial performance within energy companies in Indonesia and Malaysia from 2020 to 2023. The study utilizes data sourced from annual and sustainability reports of energy firms listed on the Indonesia Stock Exchange and Bursa Malaysia. Multiple linear regression was applied as the analytical technique, with Price to Book Value (PBV) used as the indicator of financial performance. The findings reveal that overall ESG disclosure does not exert a significant impact on financial performance. Nevertheless, when assessed individually, the governance component shows a statistically significant positive effect on PBV. These outcomes offer valuable insights for regulators and companies to strengthen governance practices in ESG reporting to enhance investor appeal and support long-term firm value.